O sujeito no meio-fio : entre o desejo e seus predicados - Daniela Sevegnani Mayorca (2016)
The present work is a result of a research oriented by the ethical principles of psychoanalysis. It is a field research developed from a case study. The subject is a woman currently engaged in a social movement organization in the city of Belo Horizonte, who was previously encarcerated for 4 years while accused of being the head of a drug and firearms scheme in the city. The question laid out by the subject towards the research was that of subjective permanence, which indicated the insistent quality of drive, marked by the lack of satisfaction which animates it and the notion of trauma that centralizes the subject in the repetition circuit. The research sought to articulate these three dimensions: drive, trauma and repetition, after the concept of subject, oriented by the psychoanalytic propositions elaborated by Freud and Lacan. With Freud we deduced that the subject appears as a return effect of the drive towards its originary source where the empty knotting point between soma and psyche, instinct and desire, nature and language resides. It is the lack of satisfaction that which inspires the drive dynamics. In Lacan, the subject comes as an effect of the gaps between representations and significants. In this sense there's only cause for that which limps. That which causes drive, as well as the subject that's its effect, is the imprint of absence: the object a. It is around it that the repetition orients itself. Therefore, we see that in the very material core of the subject concept the mythical object is to be found, necessarily lost, and in it, the hollow part of desire, the creating chasm. Through this research we walk the curb between singularity and politics, desire and ideal, drive and language, in the subject's constitution.